SYSTEM OF RICE INTENSIFICATION (SRI) PRODUCT VALUE ADDED AND DISTRIBUTION CHANNEL ANALYSIS Case Study of Handling and Post Harvesting Processes in Sudimoro, Megaluh, Jombang. - Tatiek Koerniawati Andajani; Rini Dwi Astuti (UPT Penerbitan Universitas Jember, 2012)
Indonesia was been predominantly an agricultural economy in which rice was been the major crop and staple food. Great efforts were therefore being made to improve paddyproduction and post production practices. This research was aimed to: 1)identify the addedvalue of paddy handling and post harvesting processes; 2) analyze profit margin gained byfarmer from selling off the paddy with and without handling and post harvesting process;3)describe the variability of distribution channel and marketing institution of rice, husk andbran. This research was conducted in Sudimoro village and used primary data collected form 70 SRI (System of Rice Intensification) farmers. Research findings showed that the amount of added value earned is less than 15%. The hulled rice added value is higher thanadded value of husk and bran. There were three kind of distribution channel. Themarketing institution involved were farmers, brokers, rice milling unit (RMU), wholesaler,distributor and retailer.